"IF I DON'T COOK ANYTHING OR BRING IT FOR LUNCH, THEN I SKIP LUNCH…BECAUSE WE'RE SURROUNDED BY FAST FOOD PLACES". (11th November 2018) - Lammie, S; Halpin, S N; Marconi, V C; Cooper, H; Holstad, M; Perkins, M M
Abstract: Few studies have examined nutrition and resilience among older persons living with HIV. We interviewed 20 patients aged 50 and older who were recruited using maximum variation sampling at an urban safety net HIV clinic between September and December 2016. Data collection included digitally-recorded semi-structured interviews, social network mapping, and sociodemographic and health surveys. Qualitative data were analyzed using thematic analysis. Paralleling the clinic population, most participants were African American (95%) and male (70%), with a mean age of 56 years. We identified five themes related to nutrition, health, and social determinants of health: difficulty accessing desirable or nutritious food, community and food assistance program support, socioemotional aspects of food, stocking up, and adjustment of eating habits to manage health. This aging patient population is at substantial risk for adverse health outcomes. Interventions providing access to wholesome food, like initiatives increasing healthy food purchasing power, should be considered.